Standalone Balloon Dilation versus Sinus Surgery for Chronic Rhinosinusitis: A Prospective, Multicenter, Randomized, Controlled Trial with 1-year Follow-up. Issue 4 (July 2014) - Bikhazi, Nadim; Light, Joshua; Truitt, Theodore; Schwartz, Michael; Cutler, Jeffrey; ,
Background: The objective of this prospective, multicenter, randomized trial was to evaluate and compare 1-year outcomes from the REMODEL study between office balloon dilation and functional endoscopic sinus surgery (FESS). Methods: Adults with maxillary chronic rhinosinusitis (CRS), including those with anterior ethmoid disease, who failed medical management and were surgical candidates for FESS, underwent either standalone balloon dilation or FESS in a 1:1 randomization scheme and were followed through a minimum of 1 year. Sinonasal symptom improvement was assessed using the validated 20-item Sino-Nasal Outcome Test (SNOT-20) survey. Standardized effect sizes were computed to further assess clinical significance. Ostial patency rate, rhinosinusitis episode frequency, impact of sinus disease on activity and work productivity using the validated Work Productivity and Activity Impairment survey, complications, and revision rate were also compared between the two groups. Results: Ninety-two patients (50 balloon dilation; 42 FESS) were treated and 89 (96 %) completed 1-year follow-up. Both groups showed clinically meaningful and statistically significant (p < 0.0001) improvement in mean overall SNOT-20 scores and in all four SNOT-20 subscales. The 1-year mean change in SNOT-20 after balloon dilation (-1.64) was noninferior to FESS (-1.65; p < 0.001). The standardized effect size was large, showing clinically significant improvement for both interventions. Ostial patency was 96.7 and 98.7% after balloon dilation and FESS, respectively, and each group reported significant reductions (p < 0.0001) in rhinosinusitis episodes (mean decrease, 4.2 for balloon dilation and 3.5 for FESS). Overall work productivity and daily activity impairment due to chronic sinusitis were significantly improved (p < 0.001) in both groups. There were no complications and revision surgery rate was 2% in each arm through 1 year. Conclusion: With 1-year follow-up, standalone balloon dilation is as effect as FESS in the treatment of CRS in patients with maxillary sinus disease with or without anterior ethmoid disease who failed medical therapy and met the criteria for medically necessary FESS.